Soils in the bipartite sediments within the Moscow glacial limits of the Russian Plain: Sedimentary environment, pedogenesis, paleolandscape implication. (15th January 2019) - Makeev, Alexander; Kust, Pavel; Lebedeva, Marina; Rusakov, Alexey; Terhorst, Birgit; Yakusheva, Tatiana
Abstract: The basal tills of the Late Moscow (MIS 6) Cryochrone form an important component of landscapes in northern Europe, including the center of the Russian Plain. The till is often covered only with a thin cover layer (30–50 cm as an average) – veneers of sands, sandy loams or silty loams, so that surface soils (Retisols) are formed in the bipartite sediments. The study of such soils allows identifying a set of pre-depositional, syn-depositional and post-depositional (pedogenic and cryogenic) features. An assemblage of (macro, meso and micro) morphological features together with analytical data confirmed that soils had been formed within several climatic cycles starting from the Late Moscow time till now, including the last Thermochrone, when the well-developed Argic horizon had been formed. Modern pedogenesis forms embedded profiles within the cover layer depending on the bioclimatic parameters (with Humic, Protospodic or Cambic horizons). The clear record of the final stages of sedimentation and ancient pedogenesis within profiles of soils in bipartite sediments may help to derive paleoclimatic interpretations from the last interglacial - glacial cycle till present. Correlation of these records with other archives in glacial and periglacial areas opens attractive research perspectives. Highlights: The mantle of the bipartite sediments that retain their initial features confirm that the topography of the moraine plains was only locally influenced by surface erosion and keeps record of depositional episodes since Moscow Cryochrone. A set of pre-depositional, syn-depositional and post depositional features have been identified in bipartite sediments within the Moscow glacial limits. The bipartite sediments are influenced by pedogenesis since late Moscow time and form an important paleogeographic archive with palimpsest soil memory. The features of the last Thermochrone and the Holocene pedogenesis together with frost features of the last Cryochrone are identified.